Investigation of the Effects of Hook Size and Bait Type on the Catch of Whiting, Merlangius merlangus (Linnaeus, 1758) (Gadidae) in Bottom Longline Fisheries of the Black Sea - Bünyamin Arı; İsmet Balık (Aquatic Sciences and Engineering, 2021)
This study was carried out along the Ünye coasts of the South-eastern Black Sea (Turkey), in order to investigate the effects of hook size and bait type on the catch of whiting, Merlangius merlangus(Linnaeus, 1758) (Gadidae) in the bottom longline fisheries. For this, a set of bottom longline with a total of a hundred hooks, including 20 from each hook number 2, 4, 6, 8 and 10, was tested in a total of 24 trials twice a month between March 2017 and February 2018. Each hook type was baited with squid, horse mackerel, chicken breast and whiting. During the study, a total of 373 whiting were caught. Most of the whiting catch was obtained with the hook no 2. With the reduction in hook size, both the amount of catch and the size of the fish caught decreased. Most whiting were-caught by the hooks baited with squid. This was followed by the hooks baited with horse mackerel, chicken breast and whiting, respectively. This result shows that hook size no 2 or larger should be used for catching whiting when using bottom longline in the Ünye coasts of the South-eastern Black Sea. Howev-er, considering the bait types used in this study, it is recommended to use squid as bait. If squid is thought to increase the cost of fishing, alternatively horse mackerel or chicken breast can also be used as bait.